2021
DOI: 10.1002/chir.23364
|View full text |Cite|
|
Sign up to set email alerts
|

Ligand‐stereoselective allosteric activation of cold‐sensing TRPM8 channels by an H‐bonded homochiral menthol dimer with head‐to‐head or head‐to‐tail

Abstract: Both menthol and its analog WS-12 share the same hydrophobic intra-subunit binding pocket between a voltage-sensor-like domain and a TRP domain in a cold-sensing TRPM8 channel. However, unlike WS-12, menthol upregulates TRPM8 with a low efficacy but a high coefficient of a dose response at membrane hyperpolarization and with ligand stereoselectivity at membrane depolarization. The underlying mechanisms are unknown. Here, this in silico research suggested that the ligand-stereoselective sequential cooperativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…Inter-domain non-covalent interactions have been reported to regulate the gating pathway of ion channels at room temperatures. [16, 34, 40-48] Here, this study further demonstrates that the largest and smaller hairpins along the gating pathway play critical roles in regulating a series of biochemical reaction networks to initiate a temperature threshold and to stabilize the thermal activity of the heat-sensing TRPV1 channel, respectively. Further investigation is necessary to extend to other thermosensitive TRP channels.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Inter-domain non-covalent interactions have been reported to regulate the gating pathway of ion channels at room temperatures. [16, 34, 40-48] Here, this study further demonstrates that the largest and smaller hairpins along the gating pathway play critical roles in regulating a series of biochemical reaction networks to initiate a temperature threshold and to stabilize the thermal activity of the heat-sensing TRPV1 channel, respectively. Further investigation is necessary to extend to other thermosensitive TRP channels.…”
Section: Discussionmentioning
confidence: 63%
“…The prior study suggested that F435 on S1, F516 on S3, Y545 and Y555 and R557 may form a putative menthol pocket in human TRPV1 (hTRPV1). [34] Since menthol only partly stop the heat activation of TRPV1 without changing the temperature threshold, [35][36] this putative menthol site may not alter the largest hairpin with a 21-residue loop in the VSLD/TRP/pre-S1/VSLD interfaces but may weaken the heat-sensitive R557-E570 H-bond. [25,27] Other chemical stimuli have been reported to lower the temperature threshold of mTRPV1 to a different extent in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…19 , Thus, in addition to H-bonding with R841, an H-bonded homochiral menthol dimer with head-to-head or head-to-tail is still required to push Y1005 against the anchors L841 and I844 on S4 of mTRPM8 for those experimental observations. 20 In this way, the tighter interaction between PIP 2 and TRPM8 may be allowed to increase the melting temperature threshold for channel opening. Further structural data are necessary to reveal the LPLs or menthol sites and their roles in stimulating TRPM8 opening at higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…1-2, 12-18 However, some menthol-sensitive residues such as Y745 and Y1005 in mouse TRPM8 (mTRPM8) are insensitive to cold, challenging the same gating pathway. 19, 20 On the other hand, the cold activation of TRPM8 exhibits a high temperature sensitivity Q 10 of 24-35 (the ratio of rates or open probabilities (P o ) of an ion channel measured 10 °C apart) at the physiological condition. 12, 21 Although the cryo-electron microscopy (cryo-EM) structures of closed and open mTRPM8 at 20 °C are available in the absence or presence of Ca 2+ , PIP 2 , and chemical agents such as cryosim-3 (C3) and allyl isothiocyanate (AITC), 22 the precise structural factor or motif for the specific PIP 2 -dependent cold temperature threshold and sensitivity is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…When elevated temperature decreases the menthol-evoked activity of TRPM8, or menthol increases the temperature threshold and the maximal activity temperature of rat TRPM8 (rTRPM8) from 22-26 • C and 8.2 • C to 30-32 • C and 15.6 • C, respectively, the same gating pathway seems to be shared [1,2,[12][13][14][15][16][17][18]. However, some menthol-sensitive residues, such as Y745 and Y1005 in mouse TRPM8 (mTRPM8), are insensitive to cold, challenging the same gating pathway [19,20]. On the other hand, the cold activation of TRPM8 exhibits a high temperature sensitivity Q 10 of 24-35 (the ratio of rates or open probabilities (P o ) of an ion channel measured 10 • C apart) at the physiological condition [11,12,21].…”
Section: Introductionmentioning
confidence: 99%